Prediction of intermittent cycling performance at altitude from sea level critical power - Townsend, N.; Nichols, D.; Racinais, S.; Skiba, P.; Periard, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The dose-response effect of altitude has been examined previously for VO2max (Wehrlin & Hallen, 2006); but not critical power (CP) and work performed above CP (W`). The aim of this study was to develop an altitude prediction model of CP and W` requiring sea level values only for use in the work-balance intermittent CP model (W BAL model) at any altitude. Methods: Nine trained, male cyclists (mean ± SD; age 34 ± 6 yr, V O2peak 4.57 ± 0.47 L.min-1) completed a series of 3 cycling time trials (TT; 12, 7 and 3 min), to determine critical power (CP) and work performed above CP (W ) at five simulated altitudes (250, 1250, 2250, 3250 and 4250 m). Least squares regression was used to establish a prediction model of CP and W` for altitudes up to 4250 m. On separate days, an intermittent exercise test incorporating three `all out` sprints followed by a 3 min TT was performed at 250 m and 2250 m. Predicted and actual CP + W` at 2250 m were used to compute W remaining in the intermittent test using both the differential (W BALdiff) and integral (W BALint) forms of the W BAL model. Mixed linear modeling was used to assess the effect of altitude on CP and W`, and t-tests were used to examine differences between predicted or actual modeled W BAL, and versus a criterion value of 0 kJ at end test. Results: Critical power decreased significantly at all altitudes (P<0.001), which was described by a 3rd order polynomial function (R2 = 0.99). A significant decline in W` was also found, but only at 3250 m (P=0.03) and 4250 m (P=0.01). A double-linear function characterised the effect of altitude on W` (R2 = 0.99). Upon completion of the 3 min TT in the intermittent test at 2250 m, W BALdiff computed from actual (-1.29 ± 3.48 kJ) was not different to predicted (-1.08 ± 3.27 kJ; P=0.65). Also, W BALint was not different between actual modeled (-2.83 ± 2.75 kJ) and predicted modeled (-2.61 ± 2.56 kJ; P=0.67). Compared to W BAL = 0 kJ at end test, no difference was found for W BALdiff at either 250 m (P=0.33) or 2250 m (P=0.30). However W BALint was underestimated at 250 m approaching significance (P=0.06), and significantly at 2250 m (P=0.02). Conclusion: The altitude prediction model for CP + W` developed in this study is suitable for use in the W BAL model under acute hypoxic conditions. The differential W BAL equation was found to model intermittent cycling performance effectively at both 250 m and 2250 m, however the integral W BAL model appeared to underestimate actual performance. We recommend use of the differential W BAL model for tasks involving maximal effort, short duration sprint intervals.